Effects of One-Shot Hyaluronic Acid Injection in Lifelong Premature Ejaculation: A Pilot Study - Anna Perri; Danilo Lofaro; Stefano Iuliano; Sabrina Bossio; Vittoria Rago; Rocco Damiano; Luigi Di Luigi; Sandro La Vignera; Nicola Mondaini; Antonio Aversa (Endocrines, 2022)
The therapeutic management of premature lifelong ejaculation (PE) ranges from behavioral therapy to pharmacological and surgical treatments. Hyaluronic Acid (HA) injection into the glans penis is a non-surgical procedure, intended to reduce glans hypersensitivity, improving the intravaginal ejaculation latency time (IELT). HA injection can be performed through different techniques that, although safe and effective, rarely can cause local complications. In this pilot uncontrolled study, we tested the effectiveness of a new technique based on a single HA injection into the frenulum of the glans, to improve IELT in a sample of patients affected by PE. We observed a significant increase of the IELT after one (median 73.3, IQR 66.2–79.9 s) and two months (66.2, 63.1–73.9) that gradually decreased at three months, remaining still significantly higher than at baseline (34.8, 30.9–37.4). PEDT and IIEF questionnaires significantly improved compared to baseline in the first two months of follow-up (p < 0.001). In conclusion, the preliminary results emerging from this pilot uncontrolled study, highlight the effectiveness of this one-shot HA injection approach, although a larger sample and longer follow-up time are needed to standardize the procedure.